Creatine supplementation and renal safety: The nephron reserve hypothesis - Kasznicki, Michał; Kamela, Mikołaj; Rogozińska, Alicja; Skrzypek, Emilia; Czechowska, Małgorzata; Łącki, Jakub; Jackowiak, Karol; Kalisiak, Michał; Micek, Natalia; Beśka, Wiktor (Quality in Sport, 2026)
Purpose: This narrative review proposes the nephron reserve hypothesis as a framework for reconciling conflicting evidence on creatine supplementation and kidney health. Materials and methods: Evidence was synthesized from meta-analyses, randomized controlled trials, animal models, and case reports identified through PubMed, Scopus, Web of Science, and Google Scholar through March 2025, with priority given to studies using creatinine-independent renal endpoints. Results: In individuals with preserved renal functional reserve, creatine at standard doses (3–5 g/day) does not impair glomerular filtration rate. Meta-analyses confirm that observed creatinine elevations reflect altered metabolic turnover rather than nephron injury. Evidence in chronic kidney disease remains sparse. Case reports of interstitial nephritis, tubular necrosis, and cast nephropathy, together with animal data from reduced-nephron-mass models, suggest creatine may unmask renal vulnerability in high-risk settings. Conclusions: Creatine safety should be assessed according to baseline renal reserve and clinical phenotype. Recommendations for compromised kidneys remain precautionary and are intended to guide risk assessment and future research.